Distinct BOLD Activation Profiles Following Central and Peripheral Oxytocin Administration in Awake Rats - Ferris, Craig F.; Yee, Jason R.; Kenkel, William M.; Dumais, Kelly Marie; Moore, Kelsey; Veenema, Alexa H.; Kulkarni, Praveen; Perkybile, Allison M.; Carter, C. Sue (Frontiers in Behavioral Neuroscience, 2015)
A growing body of literature has suggested that intranasal oxytocin (OT) or other systemic routes of administration can alter prosocial behavior, presumably by directly activating OT sensitive neural circuits in the brain. Yet there is no clear evidence that OT given peripherally can cross the blood-brain-barrier at levels sufficient to engage the OT receptor. To address this issue we examined changes in blood oxygen level dependent (BOLD) signal intensity in response to peripheral OT injections (0.1, 0.5 or 2.5 mg/kg) during functional magnetic resonance (fMRI) in awake rats imaged at 7.0 tesla. These data were compared to OT (1ug/5 µl) given directly to the brain via the lateral cerebroventricle. Using a 3D annotated MRI atlas of the rat brain segmented into 171 brain areas and computational analysis we reconstructed the distributed integrated neural circuits identified with BOLD fMRI following central and peripheral OT. Both routes of administration caused significant changes in BOLD signal within the first 10 min of administration. As expected, central OT activated a majority of brain areas known to express a high density of OT receptors e.g., lateral septum, subiculum, shell of the accumbens, bed nucleus of the stria terminalis. This profile of activation was not matched by peripheral OT. The change in BOLD signal to peripheral OT did not show any discernible dose-response. Interestingly, peripheral OT affected all subdivisions of the olfactory bulb, in addition to the cerebellum and several brainstem areas relevant to the autonomic nervous system, including the solitary tract nucleus. The results from this imaging study do not support a direct central action of peripheral OT on the brain. Instead, the patterns of brain activity suggest that peripheral OT may interact at the level of the olfactory bulb and through sensory afferents from the autonomic nervous system to influence brain activity.